Traços morfofuncionais, regeneração in vitro e bioquímica de espécies de Vellozia sob distúrbios por seca, alta temperatura e fogo - Borges, Bárbara Paula dos Santos (2022)
The morphofunctional traits make it possible to deepen the knowledge about the responses of plants to disturbances such as fire and drought, factors that characterize the rocky field, where the Velloziaceae family stands out for its abundance and adaptations to abiotic stresses. The objective was to evaluate morphofunctional traits related to environmental filters fire or drought, the impact of these abiotic stresses on the biochemistry and in vitro multiplication of species of the genus Vellozia. For this purpose, 10 individuals of the six species were marked to measure morphofunctional traits and 10 plants of V. pyrantha and V. seubertiana to evaluate regenerated and new rosettes. In the laboratory, initial growth was evaluated in vitro at concentrations of MS culture medium, sucrose and activated charcoal, in vitro multiplication by osmotic stress with polyethylene glycol, sucrose and mannitol and thermal stress (140 ±3 °C) using a drying oven. There was separation into two groups according to the characteristics related to drought and fire. V. seubertiana had higher averages of regeneration and regrowth. The nutrient reduced MS with 15g of sucrose favored the initial growth in vitro. Water stress induced shoots in V. pyrantha and thermal stress in V. punctulata. The formation of a cohesive group of individuals from rocky outcrops and between species of continuous environment indicates a tradeoff between drought and fire. The success of the in vitro establishment of Vellozia depends on the composition of the culture medium and the osmotic and thermal stress were efficient in inducing in vitro vegetative reproduction in V. pyrantha and V. punctulata.